Improved de/re-hydrogenation properties of MgH2 catalyzed by graphene templated Ti–Ni–Fe nanoparticles. (12th June 2022) - Soni, Pawan K.; Bhatnagar, A.; Shukla, V.; Shaz, M.A.
Abstract: The present investigation deals with the excellent catalytic effect of graphene templated Ti–Ni–Fe nanoparticles (Ti–Ni–Fe@Gr) on de/re-hydrogenation characteristics of MgH2 . The catalytic effect of Ti–Ni–Fe@Gr on MgH2 has also been compared with Ti@Gr, Ni@Gr, and Fe@Gr. It has been found that Ti–Ni–Fe@Gr lowers the onset desorption temperature up to 252 °C with improved kinetics and cyclability for the hydrogen release and absorption from MgH2 . The presence of a multivalence environment around Mg/MgH2 has been analyzed by XPS analysis which gives the evidence of possible electronic exchange between the catalyst and Mg/MgH2 during de-/rehydrogenation. Since Mg/MgH2 and Ti–Ni–Fe are both anchored on graphene template, agglomeration detrimental to cycling is not possible. Thus negligible degradation of 0.22 wt% has been observed even after 24 cycles of de/re-hydrogenation. Highlights: The catalytic effect of Graphene templated transition metals (Ti, Ni, Fe) on de-/rehydrogenation of MgH2 /Mg has been studied. MgH2 :Ti–Ni–Fe@Gr composite shows the lowest desorption temperature in the present study. MgH2 :Ti–Ni–Fe@Gr shows good cyclic stability.